Development of Arabic Assessment for Tarkib and Qira’ah Based on Higher Order Thinking Skill - Ade Sri Wahyuni; Rahmawati Rahmawati; Yelfi Dewi; Fitri Alrasi; Bambang Bambang; Meliza Budiarti (UIN Mahmud Yunus Batusangkar, Indonesia, 2025)
In Senior High School, Arabic language assessments mostly focus on memorizing grammar rules (tarkib) and recalling information in reading comprehension (Qira’ah). This assessment does not improve students’ abilities to analyze complex texts, evaluate arguments, or apply grammatical knowledge in new contexts. In Eleventh Grade, the Tasawwuq chapter of the Arabic textbook includes only 21% Higher-Order Thinking Skills questions, while 79% focus on Lower-Order Thinking Skills, such as remembering and understanding. This study aims to develop an Arabic assessment focused on tarkib and qiraah skills. The ADDIE model was used in five steps: analysis, design, development, implementation, and evaluation. This study used a qualitative approach to collect data, including documantation and questionnaires. Data analysis used descriptive statistics. In the analysis stage, LOTS questions were identified more than HOTS questions. For the student needs analysis, a questionnaire was distributed to 60 respondents, resulting in an average score of 4.19. The design stage involved developing an outline and question matrix, creating HOTS-based questions, formulating a scoring system, and establishing a rubric. During the development stage, questions were constructed in accordance with HOTS criteria, incorporating eight specific HOTS indicators. Implementation was conducted at Madrasah Aliyah Negeri 4 Agam in the eleventh grade. Evaluation results demonstrated that the Arabic assessment for Tarkib and Qira’ah, based on Higher Order Thinking Skills, effectively enhanced the critical thinking skills of eleventh-grade students at the state madrasah aliyah, as indicated by a significance value (2-tailed) of less than 0.05.